Advances in physical rehabilitation of multiple sclerosis. Issue 3 (June 2020) - Centonze, Diego; Leocani, Letizia; Feys, Peter
Abstract : Purpose of review: Multiple sclerosis (MS) is a neurological disorder that heavily affects quality of life (QoL) and demands a multidisciplinary therapeutic approach. This includes multiple protocols and techniques of physical rehabilitation, ranging from conventional exercise paradigms to noninvasive brain stimulation (NIBS). Recently, studies showing the clinical efficacy of physical rehabilitation have remarkably increased, suggesting its disease-modifying potential. Recent findings: Studies in animal models of MS have shown that physical exercise ameliorates the main disease pathological hallmarks, acting as a pro-myelinating and immunomodulatory therapy. NIBS techniques have been successfully applied to treat pain and urinary symptoms and lower limb function and spasticity, especially in combination with physical rehabilitation. Physical rehabilitation is reported to be well tolerated and effective in improving muscle function and fitness even in more disabled patients, and to enhance balance, walking and upper limb functional movements. Moreover, the dual motor--cognitive task performance can be improved by combined training protocols. Summary: The literature here reviewed indicates the importance of clinical and preclinical research in addressing the impact of neurorehabilitation on MS disability, highlighting the need of further studies to reach a more comprehensive understanding of the mechanisms involved, the best combination of techniques and the proper timing of application.